3D‐Printed Stretchable Micro‐Supercapacitor with Remarkable Areal Performance. Issue 14 (30th January 2020) - Li, Xiran; Li, Hongpeng; Fan, Xiangqian; Shi, Xinlei; Liang, Jiajie
Abstract: While stretchable micro‐supercapacitors (MSCs) have been realized, they have suffered from limited areal electrochemical performance, thus greatly restricting their practical electronic application. Herein, a facile strategy of 3D printing and unidirectional freezing of a pseudoplastic nanocomposite gel composed of Ti3 C2 T x MXene nanosheets, manganese dioxide nanowire, silver nanowires, and fullerene to construct intrinsically stretchable MSCs with thick and honeycomb‐like porous interdigitated electrodes is introduced. The unique architecture utilizes thick electrodes and a 3D porous conductive scaffold in conjunction with interacting material properties to achieve higher loading of active materials, larger interfacial area, and faster ion transport for significantly improved areal energy and power density. Moreover, the oriented cellular scaffold with fullerene‐induced slippage cell wall structure prompts the printed electrode to withstand large deformations without breaking or exhibiting obvious performance degradation. When imbued with a polymer gel electrolyte, the 3D‐printed MSC achieves an unprecedented areal capacitance of 216.2 mF cm −2 at a scan rate of 10 mV s −1, and remains stable when stretched up to 50% and after 1000 stretch/release cycles. This intrinsically stretchable MSC also exhibits high rate capability and outstanding areal energy density of 19.2 µWh cm −2 and power density of 58.3 mW cm −2, outperforming all reported stretchable MSCs. Abstract : A strategy for constructing intrinsically stretchable micro‐supercapacitors (MSCs) with high areal electrochemical performance and desirable mechanical compliance through MXene‐AgNW‐MnONW‐C60 ink in the 3D printing and unidirectional freezing process is introduced. The 3D‐printed MSC exhibits extraordinary areal electrochemical performance and maintains its performance under up to 50% strain.